DYNAMICS OF THE PRO-INFLAMMATORY AND ANTI-INFLAMMATORY CYTOKINES DURING A WHOOPING COUGH IN CHILDREN OF THE FIRST YEAR OF LIFE - N.M. KHODZHAEVA; M.D. MADZHONOVA (Паёми Сино, 2018)
Objective: To study the state of cytokine status in the dynamics of the disease and find out its role in the course of a whooping cough in children of the first year of life.